2023
DOI: 10.3389/fimmu.2023.1101387
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of iron oxide nanoparticle-induced thromboinflammatory response using a combined human whole blood and endothelial cell model

Abstract: Iron oxide nanoparticles (IONPs) are widely used in diagnostic and therapeutic settings. Upon systemic administration, however, they are rapidly recognized by components of innate immunity, which limit their therapeutic capacity and can potentially lead to adverse side effects. IONPs were previously found to induce the inflammatory response in human whole blood, including activation of the complement system and increased secretion of cytokines. Here, we investigated the thromboinflammatory response of 10-30 nm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Nevertheless, repeated infusions of SPIONs may result in elevated iron levels that can cause tissue damage via oxidative injury (Storey et al, 2012). Several studies have indicated that SPIONs can induce pro‐inflammatory conditions such as thrombo‐inflammation (Gerogianni et al, 2023), muscle autoimmune intolerance (Lan et al, 2021), increased production of pro‐inflammatory cytokine (Dalzon et al, 2020; Gaharwar et al, 2020), and lung tissue inflammation (Sadeghi et al, 2015). Furthermore, the variable clearance of iron may affect signal contrast on subsequent radiographic examinations for several months (Neuwelt et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, repeated infusions of SPIONs may result in elevated iron levels that can cause tissue damage via oxidative injury (Storey et al, 2012). Several studies have indicated that SPIONs can induce pro‐inflammatory conditions such as thrombo‐inflammation (Gerogianni et al, 2023), muscle autoimmune intolerance (Lan et al, 2021), increased production of pro‐inflammatory cytokine (Dalzon et al, 2020; Gaharwar et al, 2020), and lung tissue inflammation (Sadeghi et al, 2015). Furthermore, the variable clearance of iron may affect signal contrast on subsequent radiographic examinations for several months (Neuwelt et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Another study found that IONPs can induce oxidative stress in cells by activating pro-inflammatory mediators, which can eventually lead to cell necrosis or apoptosis. This is due to the generation of reactive oxygen species (ROS) by IONPs, which can cause oxidative stress in cells and contribute to their anti-inflammatory effects [46].…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%